CMV Oophoritis in an AIDS Patient - Michael S. Albert; Marvin S. Amstey (Hindawi Limited, 1995)
Background: Disseminated cytomegalovirus (CMV) infection is relatively uncommon, occurring primarily in immunocompromised hosts and neonates. Patients with acquired immunodeficiency syndrome (AIDS) are the most common hosts, with symptoms secondary to lung and eye involvement. There have been no reports of symptomatic CMV infection of the pelvis in women.